Ultrafast, One-Step, Salt-Solution-Based Acoustic Synthesis of Ti(3)C(2) MXene - Ghazaly, Ahmed El (ACS Nano, 2021)
[Image: see text] The current quest for two-dimensional transition metal carbides and nitrides (MXenes) has been to circumvent the slow, hazardous, and laborious multistep synthesis procedures associated with conventional chemical MAX phase exfoliation. Here, we demonstrate a one-step synthesis method with local Ti(3)AlC(2) MAX to Ti(3)C(2)T(z) MXene conversion on the order of milliseconds, facilitated by proton production through solution dissociation under megahertz frequency acoustic excitation. These protons combined with fluorine ions from LiF to selectively etch the MAX phase into MXene, whose delamination is aided by the acoustic forcing. These results have important implications for the future applicability of MXenes, which crucially depend on the development of more efficient synthesis procedures. For proof-of-concept, we show that flexible electrodes fabricated by this method exhibit comparable electrochemical performance to that previously reported.